How Does Heart Failure Fellowship Training Influence Future Clinical Practice? An Asia-Pacific Survey - Raja Shariff, Raja Ezman; Putri, Vebiona Kartini Prima; Gan, Gary; Loh, Julian Kenrick; Lee, Derek Pok Him; Sari, Novi Yanti; Evangelista, Lauren Kay M; Cruz, Rochelle Regina; Yap, Jonathan (International journal of heart failure, 2025)
KCI Citation Count: 0